REPRESENTASI KEARIFAN LOKAL DALAM BABAD TULUNGAGUNG - Yasip Yasip (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
The focus in this research are the representation of local knowledge systems; the local valuesystems; a system of local decision-making mechanism; and a system of local solidarity groups inTulungagung Chronicle. This study uses a qualitative research that uses folklore studies. Theresearch data on the representation local knowledge in Tulungagung Chronicle are verbal datafrom the following data sources: the text transcription of kentrung recording playingTulungagung Chronicle and field notes; the text transcription of an interview with culturalstakeholders; the text transcription VCD showing Siswo Budoyo Ketoprak performance playingTulungagung Chronicle. The results of data analysis include three levels of analysis, namely theanalysis of form, meaning and function of each focus of the investigation. The final result of thisresearch is the representation of local wisdom found in the Tulungagung Chronicle which is inthe form of local knowledge systems, local value systems, systems of local decision-makingmechanism, and solidarity system of the local group. This research is meaningful particularly toimprove the understanding and beliefs of the importance of local wisdom in social life and family.It also serves as a learning medium to inculcate attitudes and behavior of Tulungagungcommunity taken from the local wisdom contained in Tulungagung chronicle.